2015
DOI: 10.1371/journal.pone.0122570
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circadian Rhythm and Metabolic Gene Profile in Rats Subjected to Advanced Light Phase Shifts

Abstract: The circadian clock regulates metabolic homeostasis and its disruption predisposes to obesity and other metabolic diseases. However, the effect of phase shifts on metabolism is not completely understood. We examined whether alterations in the circadian rhythm caused by phase shifts induce metabolic changes in crucial genes that would predispose to obesity. Three-month-old rats were maintained on a standard diet under lighting conditions with chronic phase shifts consisting of advances, delays or advances plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Therefore, access to food at equal intervals throughout the light/ dark cycle, which abolishes the daily feeding rhythm, does not reset peripheral clock rhythms. It is well known that information about light (and darkness) is very important to set the circadian clocks in the SCN and periphery (Yamazaki et al 2000;Wu et al 2008;Herichova et al 2014;Herrero et al 2015). Recently, Ikeda et al (2015) showed that the length of the light period during the light/dark cycle affects the acrophase of Per2 in kidney, liver, and salivary gland under the 6-meals-a-day feeding schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, access to food at equal intervals throughout the light/ dark cycle, which abolishes the daily feeding rhythm, does not reset peripheral clock rhythms. It is well known that information about light (and darkness) is very important to set the circadian clocks in the SCN and periphery (Yamazaki et al 2000;Wu et al 2008;Herichova et al 2014;Herrero et al 2015). Recently, Ikeda et al (2015) showed that the length of the light period during the light/dark cycle affects the acrophase of Per2 in kidney, liver, and salivary gland under the 6-meals-a-day feeding schedule.…”
Section: Discussionmentioning
confidence: 99%
“…However, even during this time of sleep deprivation, a transient peak in IL-6 occurs at 0100 hours indicating that circadian factors continue to influence IL-6 levels (Redwine and Hauger et al, 2000), and Dimitrov et al (2006) have found that monocyte production of IL-6 also peaks at 0200 hours even in the midst of sleep deprivation. Other data indicate that the chronic disruption of circadian rhythm magnifies inflammatory responses to challenge with endotoxin in an animal model of shift work or chronic jet lag (Castanon-Cervantes et al, 2010), along with an increase in inflammatory gene expression profiles in adipose tissue (Herrero et al, 2015) possibly due to disruption in the circadian clock gene Rev-erbalpha (Sato et al, 2014).…”
Section: Innate Immune System Dynamics During Nocturnal Sleep: Circadmentioning
confidence: 99%
“…Considering the important role of adipose tissue in the regulation of glucose and lipid metabolism, misalignment or perturbation of the internal adipose clock is a plausible mechanism for the development of metabolic disorders. In rodents, advance phase shift or time-restricted sleeping increases the expression of lipogenic genes in white adipose tissue (Husse et al 2012;Herrero et al 2015). Moreover, prolonged light exposure in mice leads to obesity by decreasing brown adipose tissue activity via impaired adrenergic signalling (Kooijman et al 2015).…”
Section: Disruption Of the Clock Alters Adipose Tissue Metabolismmentioning
confidence: 99%
“…; Herrero et al . ). Moreover, prolonged light exposure in mice leads to obesity by decreasing brown adipose tissue activity via impaired adrenergic signalling (Kooijman et al .…”
Section: Introductionmentioning
confidence: 97%